Forced Displacement in History: Some Recent Research - Sascha O. Becker (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2022)
Forced displacement as a consequence of wars, civil conflicts, or natural disasters does not only have contemporaneous consequences but also long-run repercussions. This eclectic overview summarizes some recent research on forced displacement in economic history. While many of the episodes covered refer to Europe, this survey points to literature across all continents. It highlights new developments, and points to gaps in the literature.
Keywords: F22; R23; D74; Q54; N30; 330; Forced Displacement; Wars; Disasters; Networks